Differentially expressed genes reflect disease-induced rather than disease-causing changes in the transcriptome - Porcu, Eleonora; Sadler, Marie C.; Lepik, Kaido; Auwerx, Chiara; Wood, Andrew R.; Weihs, Antoine; Sleiman, Maroun S. Bou; Ribeiro, Diogo M.; Bandinelli, Stefania; Tanaka, Toshiko; Nauck, Matthias; Völker, Uwe; et al. (Nature communications, 2021)
Comparing transcript levels between healthy and diseased individuals allows the identification of differentially expressed genes, which may be causes, consequences or mere correlates of the disease under scrutiny. We propose a method to decompose the observational correlation between gene expression and phenotypes driven by confounders, forward- and reverse causal effects. The bi-directional causal effects between gene expression and complex traits are obtained by Mendelian Randomization integrating summary-level data from GWAS and whole-blood eQTLs. Applying this approach to complex traits reveals that forward effects have negligible contribution. For example, BMI- and triglycerides-gene expression correlation coefficients robustly correlate with trait-to-expression causal effects ( r BMI